Outcomes of infants with a birthweight less than or equal to 500 g in Northern England: 15 years experience. (17th September 2017) - Gillone, Jenna; Banait, Nishant; Miller, Nicola; Ward Platt, Martin; Harigopal, Sundeep
Abstract: Aim: We aimed to evaluate mortality and short‐term neonatal morbidity of babies born ≤500 g cared for in the Northern Neonatal Network over a 15‐year period. Method: Using regional databases, we identified all live‐born babies ≥22 weeks gestation and ≤500 g, in North East England and North Cumbria from 1998 to 2012. We quantified major neonatal morbidities and survival to one year. Results: We identified 104 live‐born babies ≥22 weeks gestation and ≤500 g (birth prevalence 0.22/1000), of which 49 were admitted for intensive care. Overall one‐year survival was 11%, but survival for those receiving intensive care was 22%. There was significant short‐term neonatal morbidity in survivors, in particular retinopathy of prematurity and chronic lung disease. Conclusion: Survival of babies born weighing ≤500 g in this cohort remains poor despite advances in neonatal care, with considerable short‐term neonatal morbidity in survivors. This could be due to a combination of attitudes and a rather conservative approach towards resuscitation and intensive care, and the intrinsic nature of these tiny babies. Abstract :